PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWAKELAS IV SD NEGERI 007KULIM JAYAKECAMATANLUBUK BATU JAYA KABUPATEN INDRAGIRI HULU - Marlini, Lena; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve learning outcomes IPS Elementary School fourth grade students Kulim jaya 007 District of Lubuk jaya in the academic year 2014/2015. Subjects in this study were students in fourth grade Kulim jaya State 007 Kulim jaya District of Lubuk Batu Jaya Indragiri the number of students 28 students, consisting of 13 men and 15 women. This study is a Class Action Research (Classroom Actions Research) which comprises two cycles. Based on the results of research and data analysis known that an increase in the percentage of activity for teachers to get an average of 79.17% success criteria very well. Implementation of the second cycle of activities for teachers to get an average of 91.03% success criteria very well.Implementation of the first cycle of activity students gain an average of 66.67% sufficient with both criteria. Implementation of the second cycle of activity students gain an average of 95.83% success criteria very well. before implementation of cooperative learning model type Make A Match was 65.25 from 28 people who follow replicates only 12 people were completely and 16 students have not completed the completeness percentage of 42.86% with less qualification. In the first cycle UH 1 daily value increased to 68.57 students who have increased as much as 17.85%, the number of students who completed 17 students. In the second cycle increased the average value of as much as 25% to 70. The implementation of the UH 2 daily value increacentage with a percentage of 89,29%. Class declared complete when it reaches â‰¥ 80 of the number of students who reach the specified KKM is â‰¥ 70. It can be concluded that cooperative learning model Make A MatchStudent can improve learning outcomes IPS Elementary School fourth grade students Kulim Jaya 007 Kulim Jaya District of Lubuk Batu Jaya.Keywords: Make A Match, IPS Learning Outcomes